SEISMIC DAMAGE SCENARIOS IN KALAMATA (S. GREECE) - D. Kazantzidou-Firtinidou; Kassaras, I.; A. Ganas; C. Tsimi; Sakellariou, N.; S. Mourloukos; P. Stoumpos; Michalaki, K.; Giannaraki, G. (Bulletin of the Geological Society of Greece, 2016)
Damage scenarios are necessary tools for stakeholders, in order to prepare protection strategies and a total emergency post-earthquake plan. To this aim, four seismic hazard models were developed for the city of Kalamata, according to stochastic simulation of the ground motion, using site amplification functions derived from ambient noise HVSR measurements. The structural vulnerability of the city was assessed following an empirical macroseismic model, developed for the European urban environment (EMS-98). The impact of the vulnerability due to the seismic hazard potential is also investigated by means of synthetic response spectral ratios at 108 sites of the city. The expected damage grade per building block, is calculated by combining vulnerability with the respective seismic intensities, derived for the four seismic sources. The importance of the followed methodology for implementing microzonation studies is emphasized, since the expected influence of the ground motion amplification due to local soil conditions has been approximated in detail. Moreover, new fragility curves for the main structural types in Kalamata are proposed for each seismic scenario.
Keywords: damage grades; Deterministic Seismic Hazard Assessment; Macroseismic vulnerability; microtremors; seismic risk models